PT. Laju Banyu Semesta digital marketing communication strategy of Sidat - Putra, Aldo Aditya (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2023)
Due to the lack of education and literacy, the public has yet to consume the Sidat (Anguilla sp) commodity widely. One company that is active in introducing Sidat is PT. Laju Banyu Semesta (Sidat Labas). This study aimed to determine the digital marketing communication strategy carried out by Sidat Labas. This research method is descriptive qualitative with an interpretive paradigm. Researchers conducted observations, documentation, and interviews with the general manager and marketing manager of Sidat Labas as well as several followers of Labas social media, which were determined by purposive sampling technique. This study uses the Computer-Mediated Communication (CMC) theory and SOSTAC Analysis from PR Smith. This research results show that PT. Laju Banyu Semesta implemented a digital marketing communication strategy targeting all groups. Message delivery is age-appropriate and spread across different social media platforms. Digital marketing communication messages are packaged in graphic designs and videos; some are delivered during ES Talk activities. In addition to conveying information, the message conveyed is a form of multi-dimensional communication to guide public perceptions about Sidat. The popularity of Sidat is still very low, and policies and collaboration with related agencies that still need to be comprehensive are obstacles in delivering messages. PT. Laju Banyu Semesta has done four of the ten tactics that PR Smith did.